Fluid therapy in burns - Sjöberg, Folke (Acta medica Lituanica, 2012)
Outcome after burn injury, as also paralleled by other trauma, has been improving steadily over the years. In this aspect a significant improvement was seen especially in the 1970-ties when the 50% survival chance from a burn injury increased from 45% total body surface area burned (TBSA%) in a 21 year old patient up to almost 80% (TBSA%). Although this improvement may be claimed to have many reasons, a significant one that needs to be stressed is the introduction of more thorough use of protocolized fluid treatment strategies
Keywords: fluid therapy; burns; survival